EFEK AROMA TERAPI LAVENDER UNTUK MENGURANGI NYERI MASA NIFAS PADA PERSALINAN NORMAL - Nur Sa’idah; Sthepani Sari Hidayat; Sonia Chairunnisa; Fitri Adriani; Elvi Tiana; Zuriani Zuriani (Pusat Riset dan Inovasi Nasional, 2022)
Trauma to the perineum can also cause discomfort and pain during sexual intercourse, so it is essential to treat this pain. One way to reduce feelings of pain is to do complementary therapy using lavender oil aromatherapy. Lavender contains antidepressant, calming, anti-anxiolytic and anticonvulsant properties. This study aimed to determine the effect of lavender aromatherapy on the intensity of perineal suture pain in postpartum mothers. Methods: The method applied is a quasi-experimental case study pretest and posttest where the research sample is the postpartum mother, Ny. Laila Tus Syania G2P2A0 2 hours postpartum with 2-degree laceration at the Independent Practice Midwife Nursaidah Batam City. The instrument in this study uses a Visual Analogue Scale (VAS) scale in the range 0-7, where no pain is worth 0, mild pain on a 1-3 scale, moderate pain 4-5, and severe pain 6-7. The material used in this study was 100% concentrated lavender oil vapor, which was dripped in several 4-5 drops and then dissolved in 200 ml of water for 30 minutes. The results showed an effect before being given lavender aromatherapy inhalation, and the maternal perineal pain score reached 7 (high or severe pain). After being given lavender aromatherapy inhalation, the maternal perineal pain score became 3 (mild pain). The conclusion from the case study is that giving inhaled lavender aromatherapy affects postpartum mothers' perineal suture pain.